The Dickens critics - Lane, Lauriat, 1925-2005 (Cornell University Press, 1961)
The present volume offers a new and different kind of aid to readers and students of Dickens' fiction. It brings together a selection of the important essays, articles, and chapters, from 1841 to now, that critically examine Dickens' fiction. With this collection the modern reader can test his own responses to Dickens against those of others -- sometimes hostile, sometimes friendly, but always lively and suggestive.